Analysis of the New Demand-Responsive Transport in Goiânia, Goiás: Citybus 2.0 - Guimarães, Bruna Rodrigues; Pasqualetto, Antonio (Revista Nacional de Gerenciamento de Cidades, 2021)
The demand-responsive public transport Citybus 2.0 was an innovation not only for Goiânia, but for all of Latin America. Created in 2019, this new way of getting around the city is intended to be a substitute for individual motorized transport, encouraging sustainable urban mobility. In order to analyze this new means of transport in the capital of Goiás, an online questionnaire was applied, which had 217 responses, of which 130 are users and 87 are non-users. The questionnaire had ten questions, two of which were general and eight with the purpose of collecting information on user satisfaction regarding the service provided by the new mode of transport. As for the perception of satisfaction, the items related to the cost and service range had the worst ratings.